Papal jurisprudence, 385-1234: social origins and medieval reception of canon law - D'Avray, D. L. (Cambridge University Press, 2022)
Why did bishops turn to the papacy for advice in late Antiquity? And what does the reception of these decretals reveal about the legal and religious culture of the mid-thirteenth century? This interpretative volume seeks to explain the first decretal age of late antiquity, placing the increased demand for papal jurisprudence - long before it exerted its influence through religious fear - within its social broad context. D. L. d'Avray then traces the reception of this jurisprudence through to the mid-thirteenth century, and the post-Gratian decretal age. Along the way he explores the role of Charlemagne and 'Pseudo-Isidore', which included many genuine early decretals alongside forged ones. Similarities between the Latin world c. 400 and c. 1200 thus help explain parallels between the two decretal ages. This book also analyses decretals from both ages in chapters on pagan marriages, clerics in minor orders, and episcopal elections. For both ages the relation between canon law and other religious genres is elucidated, demonstrating many fascinating parallels and connections.